Effects of high temperature on morphophysiological, ultrastructural, and biochemical parameters during the germination of two forest species - Reis, Luciane Pereira (2021)
Climate change resulting from anthropogenic actions has increased global temperature. These temperature increases will likely influence the survival of part of the species. Among the environmental factors, the temperature is one of the most critical for affecting the physiological, biochemical, and molecular factors of the seed. Temperature increases is considered one of the environmental factors that help in the overproduction of reactive oxygen species (ROS). The urgency of understanding seed responses to climate change is particularly important. A detailed overview of seed responses to heat stress can help formulate appropriate strategies for species conservation and preservation. Knowledge about the capacity of forest seeds to deal with temperature changes is still scarce. In this sense, the objectives of this work were: 1. To investigate the morphophysiological, biochemical, and ultrastructural changes during germination of Melanoxylon brauna seeds under heat stress; 2. Evaluate the effects of temperature on morphology, generation of ROS, antioxidant system, and mobilization of reserves in Ormosia coarctata seeds; 3. Characterize the effects of diphenyleneiodonium (DPI) on M. brauna germination, internal anatomy, hydrogen peroxide (H 2 O 2 ) content, and activity of reserve enzymes and antioxidant enzymes under optimal conditions (25 °C) and stress by heat (40°C). To evaluate the internal morphology the seeds were radiographed. Ultrastructural and anatomical parameters were evaluated using transmission electron microscopy and light microscopy. ROS production, malondialdehyde (MDA) and glucose content, carbonyl proteins, and enzyme activity (superoxide dismutase - SOD, ascorbate peroxidase - APX, catalase - CAT, peroxidase - POX, glucose-6-phosphate dehydrogenase - G6PDH, lipase, α- and β-amylase and protease) were measured by spectrophotometric analysis. The high temperature causes a reduction in the percentage and speed of germination and affects the internal morphology of M. brauna and O. coarctcta seeds. In M. brauna seeds, heat stress decreases respiratory rates and compromises the structure of mitochondria. ROS content and protein carbonylation in seeds submitted to 40 °C increased in relation to 25 °C and 35°C. The activities of the enzymes SOD, APX, CAT, and POX were significantly reduced in seeds subjected to heat stress. Glucose content, G6PDH (M. brauna), and lipase activity also decreased in seeds exposed to high- temperature stress. Seed exposure to DPI decreased germination percentage at 25 °C and does not affect germination at 40 °C. DPI caused less reduction in the loosening of the outer layers of the integument and reduced the H 2 O 2 content and activity of all tested enzymes. In summary, heat stress negatively affects germination, promotes oxidative stress, and induces damage to mitochondrial ultrastructure, seed morphology, and anatomy. The data obtained in this study contribute to a better understanding of the effects of high temperatures on the germination of native seeds, in addition to showing the contribution of ROS to germination. Keywords: Climate change. Heat stress. Melanoxylon brauna. Ormosia coarctata.